Philosophical revolution and the shaping of European consciousness: Bertrando Spaventa’s La filosofia italiana nelle sue relazioni con la filosofia europea - Fernanda Gallo (Rosenberg & Sellier, 2015)
The relevance that Bertrando Spaventa gave to the role of philosophy in the construction of a moral and political Italian consciousness and, more in general, of a European one, is still useful to reflect on the relationship between philosophy and the future of Europe. In this paper I reviewed Spaventa’s work La filosofia italiana nelle sue relazioni con la filosofia europea (1862), where the author recognized how important it was to rekindle in Italian citizens the ancient idea of moral liberty, conceptualized during the Renaissance, in order to provide the political input for the creation of Italians.